AB0163 The influence of clinical and genetic variables on methotrexate effectiveness in portuguese rheumatoid arthritis patients. (23rd January 2014) - Lima, A.; Bernardes, M.; Monteiro, J.; Azevedo, R.; Costa, L.; Ventura, F.; Seabra, V.; Medeiros, R.
Abstract : Background: Methotrexate is the mainstay DMARD in RA treatment 1 . Despite its effectiveness, additional DMARDs are often required to achieve the recommended goals of low disease activity/remission 1 . Given the clinical implications of widespread use of MTX in RA, many studies were conducted to evaluate the role of potential biomarkers in predicting effectiveness of MTX 2, 3 . Nevertheless, there is scant information regarding the Portuguese population. Objectives: To determine possible associations of MTX effectiveness with clinical and genetic variables in Portuguese RA patients. Methods: Patients (n=233) with active RA treated with MTX following treatment guidelines were monitored from 2009. Twenty-six clinical variables possibly influencing disease state and drug response and six polymorphisms related with MTX metabolism (rs1801133, rs4673993, rs34743033, rs2853542, rs34489327 and rs1051266) were analyzed. Variables were compared between nonresponders (nResp)/responders (Resp). NResp were defined with a DAS28>5.1 in two consecutive evaluations despite high-dose MTX. Statistical analysis (significance at P <0.05) were performed using Student's t-test, Mann-Whitney U test or χ 2 test. Differences in genotype distribution groups were tested by 2x2 cross-tabulations for carriers vs noncarriers followed by 2-sided χ 2 test analysis. Results: Clinical variables : smokers had a higher probability to be Resp ( P =0.009); lower age at diagnosis and higher duration of disease were related with nResp ( P =0.046 and 0.008, respectively); anti-CCP and ANA's positive patients had a higher probability to be nResp ( P =0.005 and 0.007, respectively); a higher DAS28 was associated with nResp ( P =0.001 and 0.029, respectively); considering the individual variables to DAS28, higher TJC and SJC were related with nResp and higher PCR levels were associated with Resp ( P =0.002, 0.001 and 0.035, respectively); higher HAQ score was related with nResp ( P =0.005); the NSAIDs users had higher probability to be nResp ( P =0.002). Genetic variables: homozygous TT for MTHFR C677T and 3R3R for TYMS 28bpVNTR, patients carrying T allele for ATIC C675T and 6bp- allele for TYMS 1494del6 were more likely to be nResp ( P =0.049, 0.007, 0.025 and 0.023, respectively). Moreover, patients carrying C allele for MTHFR C677T and 2R allele for TYMS 28bpVNTR, and homozygous CC for ATIC C675T and 6bp+6bp+ for TYMS 1494del6 were more likely to be Resp ( P =0.049, 0.007, 0.025 and 0.023, respectively). No statistical differences between Resp/nResp were found for the other studied variables. Conclusions: Polymorphism in MTHFR, ATIC and TYMS genes are related with MTX effectiveness. Thus, genotyping may help to identify patients whom will benefit from MTX-treatment and assist clinicians to make criterious treatment decisions. References: Hider, S.L. et al. The pharmacogenetics of methotrexate. Rheumatology, 2007. Katchamart, W. et al. Predictors for remission in rheumatoid arthritis patients:A systematic review. Arthritis Care Res, 2010. Dervieux, T. et al. Pharmacogenomic and metabolic biomarkers in the folate pathway and their association with methotrexate effects during dosage escalation in rheumatoid arthritis. Arthritis Rheum, 2006. Disclosure of Interest: None Declared